Investigation of the Origin of Voltage Generation in Potentized Homeopathic Medicine through Raman Spectroscopy - Bhattacharya, Tara Shankar; Maitra, Payaswini; Bera, Debbethi; Das, Kaushik; Bandyopadhyay, Poonam; Das, Sukhen; Shankar Bhar, Durga; Singha, Achintya; Nandy, Papiya (Homeopathy, 2019)
Background For the study of homeopathic medicines in proper perspective, emerging techniques in material science are being used. Vibrational spectroscopy is one such tool for providing information on different states of hydrogen bonding as an effect of potentization. The associated change in electrical properties is also correlated with this effect.Objective From the vibrational spectra, the changes in hydrogen bonding due to dilution followed by unidirectional vigorous shaking (together termed potentization) of 91% ethanol and two homeopathic medicines Chininum purum and Acidum benzoicum have been studied. The aim was to correlate the result with the change in the electrical properties of the system.Methods Raman spectroscopy was used to study the vibrational spectra. A U-shaped glass tube (electrochemical cell), where one arm contained bi-distilled water and the other arm alcohol/homeopathic medicine (the arms being separated by a platinum foil), was used to measure the voltage generated across two symmetrically placed platinum electrodes.Results For all samples, it was observed that potentization affected the intensity of OH stretching bands at the frequencies 3240 cm−1, 3420 cm−1 and 3620 cm−1, corresponding to strong hydrogen bond, weak hydrogen bond and broken hydrogen bond, respectively. With the increase in potency, in the presence and absence of the two medicines in ethanol, the number of OH groups linked by strong hydrogen bonds decreased, while the number of OH groups with weak hydrogen bonds increased. With the increase in potentization, the number of OH groups with broken hydrogen bonds showed a difference in the presence and absence of the medicine.The voltage measurements for ethanol show that, with succussion, the magnitude of voltage increased with the two medicines at lower potencies, but not at higher potency where the voltage is lower. Acidum benzoicum, which is acidic in nature, had higher voltage values (113mV, 130 mV and 118 mV at 6C, 30C and 200C, respectively), compared with Chininum purum, which is basic in nature (20 mV, 85 mV and 65 mV at 6C, 30C and 200C, respectively).Conclusion The experimental results indicate a correlation between the vibrational and electrical properties of the homeopathic medicines Acidum benzoicum and Chininum purum at different potencies.
Keywords: Raman spectroscopy; hydrogen bonding; voltage generation; homeopathic medicines; potentization